Sexual attraction and childhood association a Chinese brief for Edward Westermarck - Wolf, Arthur P. 1932-2015 (Stanford Univ. Press, 1995)
Freud's challenge carried the day and became the standard view throughout the social and biological sciences. Consequently, the question was: why do all societies repress this natural inclination? Biologists argued that the incest taboo protected us from dangers of inbreeding; sociologists argued that it was necessary to prevent sexual rivalry that would destroy the family; and anthropologists saw the real purpose of the taboo as forcing families to exchange women in marriage
Keywords: Westermarck, Edward <1862-1939> -- Philosophy; Abus sexuels à l'égard des enfants - Chine; Costumbres sexuales - China (República Popular, 1949); Crueldad con los niños - China (República Popular, 1949); Inceste - Chine; Incesto - China (República Popular, 1949); Mariage - Chine; Sexo en el matrimonio - China (República Popular, 1949); Tabú - China (República Popular, 1949); Alltag, Brauchtum; Philosophie; Child abuse -- China; Incest -- China; Marriage customs and rites -- China; Sex in marriage -- China; Sexual attraction -- China; Taboo -- China; Sexualität; Ehe; China (República Popular, 1949) - Vida social y costumbres; Chine - Moeurs et coutumes; China -- Social life and customs; China